Scanning electron microscopic-studies on ependymal surface of brain ventricles in goat - KUMARI, PAWAN; KUMAR, SURAJ; SINGH, YASHWANT (The Indian Journal of Animal Sciences, 2013)
The III ventricle roof of goat brain in its mid portion presented synchronous wave like dense arrangement of cilia. However, its extensi n towards pineal recc:s.s had transitions zone with the predominance of microÂ· villi, supraependymal cells and neurons of different shapes. The clba oflateral ventricle were arranged star like whereas, those of IV ventricle were tortuous. Micro:villi, apical blebs and supraependymal cells were present irregularly in between cilia. The cilia were regular and smooth in different parts of ventricles except cilia ofIV ventricle which had irregular surface. Most of cilia had knob like free endings.